2020
DOI: 10.1038/s41598-020-64134-w
|View full text |Cite
|
Sign up to set email alerts
|

Routine Karyotyping Reveals Frequent Mosaic Reciprocal Chromosome Translocations in Swine: Prevalence, Pedigree, and Litter Size

Abstract: In the routine commercial karyotype analysis on 5,481 boars, we identified 32 carriers of mosaic reciprocal translocations, half of which were carrying a specific recurrent translocation, mos t(7;9). An additional 7 mosaic translocations were identified through lymphocyte karyotype analysis from parents and relatives of mosaic carriers (n = 45), a control group of non-carrier boars (n = 73), and a mitogen assessment study (n = 20), bringing the total number of mosaic carriers to 39 cases. Mosaic translocations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Our cytogenetic screening in purebred boars in a commercial nucleus pig herd from Australia identified a comparatively higher (6.38%) prevalence of reciprocal translocations. This prevalence rate is similar to several other published reports in other commercial herds spanning multiple countries, such as France (0.47% in 7700 young boar), Canada (0.58% in 5481 boars), Spain (3.8% in 849 pigs) [3,6,7]. Our data also suggest an association of reduced reproductive success in the hypoprolific boars with reciprocal chromosome translocations (Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our cytogenetic screening in purebred boars in a commercial nucleus pig herd from Australia identified a comparatively higher (6.38%) prevalence of reciprocal translocations. This prevalence rate is similar to several other published reports in other commercial herds spanning multiple countries, such as France (0.47% in 7700 young boar), Canada (0.58% in 5481 boars), Spain (3.8% in 849 pigs) [3,6,7]. Our data also suggest an association of reduced reproductive success in the hypoprolific boars with reciprocal chromosome translocations (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…The semen quality assessment methods used in boar studs in Australia do not detect chromosomal rearrangements, such as RTs. The results reported in this study have identified a high incidence (6.38%) of these rearrangements in a commercial Australian boar population and appear to be higher than in other pig populations (<1-4%) [3,6,7]. A minimum of 30 matings across multiple sows is a common practice in genetic nucleus herds to ensure no maternal confounding factors are affecting terminal sire performance.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations